Pengaruh Media SoftBook Shapes Terhadap Kemampuan Anak Mengenal Bentuk Geometri Anak Usia 4-5 Tahun di TK GKPI Tarutung Kota - Wina Cindy Miranti Lumbantobing; Uranus Zamili; Emmi Silvia Herlina (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
The purpose of this study was to determine the effect of the use of SoftBook Shapes Media on Children's Ability to Recognize Geometric Shapes of Children Aged 4-5 Years in GKPI Kindergarten Tarutung City. The research hypothesis is: "The use of Softbook Shapes media has an effect on the ability to recognize geometric shapes of children aged 4-5 years in GKPI Kindergarten Tarutung City". The population was all students of GKPI Kindergarten Tarutung City as many as 128 people. The research sample was determined using the Random Sampling technique, namely 21 students of Kindergarten A as an experimental class using SoftBook Shapes Media and 24 students of Kindergarten B1 as a control class using ordinary treatment (conventional class). This research method is a quasi-experimental design method with a Nonequivalent Control Group Design design. The instrument used in this study was an observation sheet of 20 items. The research data for the questionnaire was analyzed using the average difference test formula (N-Gain Score) it is known that the average value for the experimental class is 0.7853 which is in the high category. And the average value for the control class is 0.2059 in the low category. Then conducting an independent test using the t test obtained the value of t count = 14.172> t table (α = 0.05; df = 43) = 2.021. Thus it can be concluded that the research hypothesis is accepted, namely the use of Softbook Shapes media has an effect on the ability to recognize geometric shapes of children aged 4-5 years of GKPI Tarutung City Kindergarten and H0 is rejected.